Student activities in solving mathematics problems with a computational thinking using Scratch - Neneng Aminah; Yohanes Leonardus Sukestiyarno; Adi Nur Cahyono; Siti Mistima Maat (International Journal of Evaluation and Research in Education (IJERE), 2023)
The progress of the times requires students to be able to think quickly. Student activities in learning are always associated with technology and students’ thinking activities and are expected to think computationally. Therefore, this study aimed to determine how learning with the concept of computational thinking (CT) using the Scratch program can improve students’ mathematical problem-solving abilities. An exploratory research design was conducted by involving 132 grade VIII students in Kuningan, Indonesia. Data analysis began with organization, data description, and statistical testing. The results showed that students performed the concepts of abstraction thinking, algorithmic thinking, decomposition, and evaluation in solving mathematical problems. There were differences in students’ problem-solving abilities before and after the intervention. Students’ activeness in solving problems using the CT concept through a calculator significantly affected 52.3% of the ability to solve mathematical problems.